Phylogenetic Patterns of Genus Megophrys (Anura: Megophryidae) from Java and Sumatra - Kurniawan, Nia; Affandi, Aminuddin; Wardani, Erintha Eka; Chomsy, Indah Nur; Firdaus, Anggun Sausan; Kurnianto, Agung Sih (The Journal of Experimental Life Science, 2017)
The emergence of Java and Sumatra islands at the end of Miocene, has impact to the diversity of fauna that living in the islands. Amphibia, as one of a genetic information series, can be used as a good phylogenetic comparison. Genus Megophrys (Anura: Megophryidae), is a member of amphibians that live isolated at an altitude of 1000 ASL (Above Sea Level) or more. The purpose of this research is to analyze the phylogenetic patterns of genus Megophrys in Java and Sumatra based on the analysis of 16s rRNA gene. We also analyzed the zoogeography to understand the history of relationship and the establishment of these islands. We took samples on 12 localities: 10 areas of Sumatra and 2 areas of Java. We used Qiamp Blood and Tissue Kit to extract the DNA from tissues. Qualitative analysis of DNA was done by running electrophoresis on 1% agarose gel. Qualitative analysis of DNA was done by running electrophoresis on 1% agarose gel. Results show that Clade A has 2 subclasses: I and II. Subclade I consists of Sumatran specimens, whereas subclade II consists of Javanese specimens. Subclaude I and II have paraphyletic connections. Clade B classified as politomy clade consists of Megophrys sp. from West Pasaman, Megophrys sp. from West Sumatra and Megophrys sp. from Pasawaran, Lampung. The result shows that Megophrys sp. of subclade I (clade A) and clade B, belongs to the same group, both of them were originated from Sumatra. Megophrys sp. subclade I (clade A) originated from Tanggamus (Lampung) and West Lampung (Lampung) separated with 2 species of Megophrys sp. of clade B originated from Pasawaran (Lampung).Keywords: 16s rRNA, Java, Megohprys, Sumatra, zoogeography